The size of national delegations and the need for attendance regulation at climate conferences (Ökologisches Wirtschaften - Fachzeitschrift, 2016)
With the growing significance of the United Nations climate conferences the number of attendees has grown considerably over the last years. But more participants do not necessarily ensure better decisions. And sometimes attending a United Nations climate conference is only a way to raise the profile of the attendee.